The effect of local Universe constraints on halo abundance and clustering - Hutt, ML; Desmond, H; Devriendt, J; Slyz, A (Oxford University Press, 2022)
Cosmological N-body simulations of the dark matter component of the universe typically use initial conditions with a fixed power spectrum and random phases of the density field, leading to structure consistent with the local distribution of galaxies only in a statistical sense. It is, however, possible to infer the initial phases which lead to the configuration of galaxies and clusters that we see around us. We analyse the CSiBORG suite of 101 simulations, formed by constraining the density field within 155 Mpc h−1 with dark matter particle mass 4.38 × 109 M⊙, to quantify the degree to which constraints imposed on 2.65 Mpc h−1 scales reduce variance in the halo mass function and halo–halo cross-correlation function on a range of scales. This is achieved by contrasting CSiBORG with a subset of the unconstrained Quijote simulations and expectations for the ΛCDM average. Using the FOF, PHEW, and HOP halofinders, we show that the CSiBORG suite beats cosmic variance at large mass scales (≳1014 M⊙ h−1), which are most strongly constrained by the initial conditions, and exhibits a significant halo–halo cross-correlation out to ∼30 Mpc h−1. Moreover, the effect of the constraints percolates down to lower mass objects and to scales below those on which they are imposed. Finally, we develop an algorithm to ‘twin’ haloes between realizations and show that approximately 50 per cent of haloes with mass greater than 1015 M⊙ h−1 can be identified in all realizations of the CSiBORG suite. We make the CSiBORG halo catalogues publicly available for future applications requiring knowledge of the local halo field.